2016
DOI: 10.18632/oncotarget.12280
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin interaction with NHERF1 and RASSF1A methylation in metastatic colorectal cancer patients

Abstract: There is an increasing need to identify new biomarkers in colorectal cancer (CRC) to further characterize this malignancy. β-catenin plays a central role in the Wnt signaling pathway. It also binds Na+/H+ exchanger regulating factor 1 (NHERF1) and interacts with the RAS-association domain family 1, isoform A (RASSF1A), but the mechanisms of this possible crosstalk are still not fully understood. In this study, we analyzed for the first time the different subcellular expression of β-catenin, NHERF1, and RASSF1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In Group 1, we observed a higher level of RASSF1A methylation in paired liver metastases than in primary tumors. In accordance with previous data, changes in DNA methylation can play a key role in the metastatic process [ 19 ]. In particular, a crucial role for RASSF1A in CRC progression has been demonstrated [ 9 , 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Group 1, we observed a higher level of RASSF1A methylation in paired liver metastases than in primary tumors. In accordance with previous data, changes in DNA methylation can play a key role in the metastatic process [ 19 ]. In particular, a crucial role for RASSF1A in CRC progression has been demonstrated [ 9 , 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…For negative control, the primary antibody was omitted and replaced by PBS 1X pH 7.6. The accuracy, reliability and reproducibility of these antibodies (β-catenin, NHERF1, TWIST1, HIF-1α and RASSF1A) have been validated in previous studies already published [ 19 , 30 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 75%
“…The immunostaining of NHERF1 and β-catenin was assessed, as previously described [12,15]. NHERF1 immunostaining was predominantly cytoplasmic, and, in some cases, intense nuclear staining was also observed.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study, which we carried out demonstrated the prognostic significance of nuclear NHERF1 expression (nNHERF1) in a cohort of patients with primary BC [13]. It is worth mentioning that NHERF1 plays a significant role during the regulation of several oncogenic signaling pathways, including Wnt/β-catenin [14,15]. Wnt/β-catenin pathway is an evolutionarily conserved pathway that controls cell proliferation, differentiation, and the maintenance of stem cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, new evidences in favor of involvement of NHERF1 in Wnt signaling pathway and consequently in CRC development have been collected. A positive correlation among RAS-association domain family 1 methylation, isoform A (RASSF1A) and nuclear β-catenin has been found too, noting that Wnt pathway activation is mediated by RASSF1A, a putative tumor suppressor RAS effector, whose epigenetic silencing by promoter methylation has been reported during cancer progression [51] , [52] . These observations support the NHERF1 limelight in the cancer development and its trigger role, given by its intrinsic nature, that makes it a highly versatile molecule.…”
Section: Introductionmentioning
confidence: 98%